2015
DOI: 10.1007/s10900-015-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, Obesity and Emotional Factors Associated With Gestational Hypertension

Abstract: Identifying factors that can be related to the occurrence of gestational arterial hypertension. The sample was composed by 105 pregnant women in their third trimester of gestation, during the period between September 2013 and August 2014. General assessment questionnaires together with a questionnaire to evaluate anxiety (STAI-A-STATE) were applied; arterial blood pressure values were collected. To classify anxiety, a mean of the final result of all the questionnaires gotten was calculated. Pregnant women who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…There was no significant association between the study outcome and the skin color / race, diverging from other studies 16,25,27,28 which observed statistical significance among black women. For the use of tobacco during gestation, the results of the present study ratify researches carried out at the national level, in Maternities of the States of the Northeast, 19 Southeast 23 and Southern Regions of Brazil, 23 as well as with research data from other countries with women of Nordic countries 26 (Sweden, Norway, Denmark, Finland and Iceland), since no significant associations were found.…”
Section: Modelscontrasting
confidence: 99%
See 1 more Smart Citation
“…There was no significant association between the study outcome and the skin color / race, diverging from other studies 16,25,27,28 which observed statistical significance among black women. For the use of tobacco during gestation, the results of the present study ratify researches carried out at the national level, in Maternities of the States of the Northeast, 19 Southeast 23 and Southern Regions of Brazil, 23 as well as with research data from other countries with women of Nordic countries 26 (Sweden, Norway, Denmark, Finland and Iceland), since no significant associations were found.…”
Section: Modelscontrasting
confidence: 99%
“…16 The results of this study identified as risk factors for the occurrence of SGHS, the absence of a partner, the inadequacy of schooling for the age and the presence of a clinical history of risk.…”
Section: Discussionmentioning
confidence: 73%
“…Obesity and depression have been cited as the most prevalent comorbidities of gestation. [33] However, the correlation between higher BMI associated to depression and the development of gestational hypertension has not been fully established yet. Moreover, in the present study, there was no correlation of BMI with PSS in the study group.…”
Section: Dicussionmentioning
confidence: 99%